La cause palestinienne entre « parler musulman » et « parler chiite », ou les transformations des imaginaires politiques dans un village du Liban-Sud - Khalila Aude Coëffic (Revue des Mondes Musulmans et de la Méditerranée)
Building on an ethnographic study of Hizbullah’s activists in a village in South Lebanon, this article explores how Lebanese Hizbullah has framed its commitment to the Palestinian cause. I show how the sacralization of the cause was meant to defuse the hostility generated by the oftentimes tense relationship between Lebanese and Palestinian inhabitants of the South. I then question how Hizbullah’s military mobilization in the war in Syria disrupted this framing process.